Peningkatan Keterampilan Kader Posyandu dalam Memantau Pertumbuhan Anak Balita pada Masa Pandemi Covid 19 - Nurul Putrie Utami; Khoiriyah Isni; Prima Suci Rohmadheny (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
The Covid-19 pandemic has resulted in the cessation of implementing the Integrated Healthcare Center (Posyandu) program in Wonokromo 1, Wonokromo, Pleret Bantul. In contrast, the early period of life, including infancy and children, is a critical period of body and brain growth. Any nutritional problems could lead to serious nutritional problems and low intelligence. Therefore, this service program aims to optimize posyandu activities by arranging the training for cadres to support toddlers’ growth in the Covid-19 pandemic era. The training included anthropometric measurements and analysis of growth charts for children under five for posyandu’s cadres. This activity was attended by 15 posyandu cadres and delivered by using discussion, simulation, and demonstration methods. It was found that the cadres still made some mistakes in measuring weight, body length, height, and head circumference, so they were given a demonstration of the correct measurement methods. The cadres are also trained to interpret the data in growth charts and explain their follow-up. The result of this activity is the enhancement in knowledge and skills in anthropometric measurements and growth charts interpretation by Posyandu’s cadres obtained from written tests and direct observations of the anthropometric measurements process and growth charts interpretation. It is expected that this activity will assist cadres in getting the correct measurement results to detect nutritional problems in toddlers quickly and accurately. Thus, they can be handled immediately and not cause severe dietary issues.